Determinants of Food Prices in Türkiye: Fourier Engle-Granger Cointegration Test - Veysel İnal; Şerif Canbay; Mustafa Kırca (İktisat Politikası Araştırmaları Dergisi)
This study aims to reveal the effects of consumer interest rates, real effective exchange rate index, and food production index on the food price index in Türkiye, in the date range 2008M04-2020M08. The relationships between the variables were investigated with the Fourier Engle-Granger (FEG) cointegration test, long-run coefficient estimators, and Fourier Granger causality tests based on the error correction model. This study uses a novel developed time series analysis while investigating the factors that cause the increase in the food price index, which has become a serious problem in Türkiye. It is the first study on this subject for Türkiye in terms of the period and the method. According to the FEG cointegration test results, it was determined that consumer interest rates, real effective exchange rates, and food production index significantly affected food prices in the long run. Over the long term, a 1% increase in the food production index decreased the food price index by 0.39% and 0.33%, and a 1% increase in the real exchange rate index reduced the food price index by 0.26% and 0.25%. Consumer interest rates did not have a significant effect. In addition, according to the Fourier Granger causality test results based on the error correction model, causality relationships from the real effective exchange rate index and food production index to the food price index were determined. The study contains important findings for policymakers.